EARNINGS MANAGEMENT AT PUBLIC COMPANIES WITH EMPLOYEE STOCK OWNERSHIP PROGRAM (ESOP) - Edy Suranta; Pratana Puspa Midiastuty; Nikmah Nikmah; Ariana Satri Andina (Journal of Economics, Business, and Accountancy Ventura, 2010)
This research investigates the significant differences of discretionary total accrual between ESOP companies and non ESOP ones as listed at Indonesia Stock Exchange (IDX), and significant differences of stock return before and after implementing ESOP as well as the significant differences of stock return in every single stage of ESOP. This research was conducted on 11 companies doing the ESOP and other 11 ones without doing the ESOP during 1999-2004. The test is by means of windows period during three years before the ESOP, in the year of ESOP taking place, and in the three years after the ESOP. The model used for examining earnings management is the modified Jones model. The proxy of earnings management is discretionary total accrual and the measurement of stock price is stock return. This research was analyzed using independent sample t test and paired sample t test. The results showed that the companies as the sample in this research did the earning management increased their income in the period of three to two years before ESOP and increase their income in the period of one year before ESOP and for the following years after the ESOP. Yet, there are no significant differences of discretionary total accrual between these two groups. There was not any evidence of significant differences of stock return before and after time of ESOP and neither significant differences of stock return in every stage of ESOP but found that negative stock return occurred after and during three stages of the ESOP.